The Settlement of Contradictory Hadith on Mahram Status for Man due to Al-Radhāah - Zikri Darussamin; Rahman Rahman; Adynata Adynata (Jurnal Ushuluddin, 2022)
This study examined the hadith regarding the determination of mahram status for adult men due to breastfeeding (al-radhāah). It was needed to be conducted because the hadiths are contradictory to one another. Using the mukhtalif al-hadith science method, this study tried to find the right and correct understanding, avoiding visible outward contradictions, with two forms of settlement, namely non-compromising and compromise. The majority of scholars prioritize a compromise settlement first, then a non-compromising one. The determination of the hadith "maqbul-ma'mulbih" and "maqbul-ghayru ma'mulbih" is a consequence of the application of non-compromising settlement through the nasakh or tarjih method approach. The findings show that contradictory hadiths on adult breastfeeding due to al-radhāah can be resolved by the compromise method (al-jam'u) using takhshis al-'am. The Prophet's command to Sahlah bint Suhail to breastfeed the adult Salim so that he becomes a mahram because of al-radhaah, is only a form of the Prophet's specialness to Salim and not for other adult men